Association between vitamin D receptor polymorphisms, tight junction proteins and clinical features of adult patients with atopic dermatitis - Teresa Grieco; Elisa Moliterni; Giovanni Paolino; Camilla Chello; Alvise Sernicola; Colin Gerard Egan; Fabrizio Nannipieri; Santina Battaglia; Marina Accoto; Erika Tirotta; Silvia Trasciatti; Silvano Bonaretti; et al. (Dermatology Practical & Conceptual, 2024)
Background: Few studies have explored the intricate connections between vitamin D receptor (VDR) gene polymorphisms, VDR, tight junction (TJ) protein expression and clinical features of atopic dermatitis (AD).